Genotype–Phenotype Correlations by Ethnicity and Mutation Location in BRCA Mutation Carriers. Issue 3 (19th March 2015) - Bayraktar, Soley; Jackson, Michelle; Gutierrez‐Barrera, Angelica M.; Liu, Diane; Meric‐Bernstam, Funda; Brandt, Amanda; Woodson, Ashley; Litton, Jennifer; Lu, Karen H.; Valero, Vicente; Arun, Banu K.
Abstract: The genotype–phenotype correlations of the specific BRCA1 and BRCA2 mutations in multi‐ethnic populations in USA have not yet been fully investigated. This study was designed to evaluate the effects of ethnicity at specific mutation locations and breast/ovarian cancer phenotypes. Our cohort included 445 women with different ethnic backgrounds who underwent BRCA genetic testing between 1997 and 2010. Known clinical and pathologic characteristics were compared with Chi‐Square Analysis or Fisher's Exact test as appropriate. The three most common mutation locations in BRCA1 (exons 2, 11, and 20) and BRCA2 (exons 10, 11, and 25) genes were chosen. Prevalence of BRCA1 exon 2 mutations were significantly higher in Ashkenazi Jewish (AJ) women compared to Caucasians (41% versus 15%; p = 0.001). Similarly, AJ women with breast cancer were more likely to have BRCA1 exon 2 mutation (47% positivity in AJ women versus 0–12.5% positivity in other ethnicities; p = 0.004). Women carrying the exon 20 BRCA1 mutation had the highest probability of having combined breast and ovarian cancers compared to women carrying other exon mutations (p = 0.05). The median age at initial cancer diagnosis, phenotypic features of breast cancer tumors, and overall survival did not vary significantly by ethnicity or mutation location. Our data suggest that ethnicity does not affect age of onset, overall survival or confer different risks of breast and ovarian cancer development in BRCA carriers. These results also suggest that women carrying the exon 20 BRCA1 mutation may warrant mutation‐specific counseling and be more aggressively managed for risk reduction.